Pengembangan Kemampuan Kemandirian Anak Melalui Permainan Egrang Batok di Kober Darussalam Samarang - Yan Yan Nurjani; Hani Hani (LP2M STAI Al-Musaddadiyah Garut, 2026)
Children's ability to be independent is one of the basic skills that children really need in socializing with friends, both in the family, school and surrounding environment. This development of independence will make children more confident in expressing their thoughts, participating in class activities, and building their social and cognitive abilities. This research began when initial observation research in Kober Darussalam showed that the condition of the children in group A had not yet reached the expected level of success. Learning media is still conventional, especially in the introduction of traditional games. The aim of this research was to determine the ability of group A Kober Darussalam to develop children's independence before and after the action using shell stilts. This research used a type of classroom action research (PTK), and the research subjects were thirteen children from group A. The research was conducted in two cycles based on the STPPA indicator for independence abilities. The data collection techniques used were interviews, documentation and observation. The results of research using shell stilts as a whole in developing children's independent abilities in group A Kober Darussalam can develop children's abilities optimally. This is shown by the percentage of children's success in each cycle, namely 23% in the pre-cycle, 31% in cycle I, and 100% in cycle II. Keywords: Early Childhood, Independence, Egrang Batok Game